Insights into FinTech (Financial Technology): A Mini Review - RUTU PADHIYAR, NAVJYOT RAVAL, ALPESH GAJERA, DHAVAL VYAS4, (European Economic Letters (EEL), 2023)
Fintech, the word, is a combination of "financial technology." When fintech emerged in the 21st century, the term was initially applied to the technology employed at the back-end systems of established financial institutions. Fintech now includes different sectors and industries such as education, retail banking, fundraising, and investment management, to name a few. The paper reviews Key Factors, Issues, and Challenges in this emerging field. In this study, thirteen papers related to this subject are illustrated and summarized for future research and studies.